2022
DOI: 10.3390/w14142152
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Isotherms and Kinetic Effects during the Adsorption of Pb(II) on Titanosilicates Compared with Natural Zeolite Clinoptilolite

Abstract: The present study focuses on the adsorption of Pb(II) by the H-form of titanosilicates (ETS-4, GTS-1) and clinoptilolite. The H-forms were prepared by first exchanging the extra-framework cations—Na+, K+, Ca2+, etc.—with NH4+, and by subsequent thermal treatment for obtaining H-forms. The purity and thermal behaviour of the initial, NH4+, and H-forms of ETS-4, GTS-1, and clinoptilolite were analysed by powder XRD, while the morphology and size of the particles were determined by SEM. The chemical composition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 88 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…However, by comparing the R 2 values, it can be determined that the adsorption behavior of 18PZ5A was more consistent with PFO and E, given that they had the same value. The PFO model assumes that adsorption is based on the adsorption capacity of the adsorbent [62], and the E model is generally applied in chemisorption processes; it assumes that the active sites of the adsorbent are heterogeneous [63]. From the value of R 2 , it cannot be determined which model better describes the adsorption since it is an independent criterion [64].…”
Section: Adsorption Isotherms Of As(v) On 11z5amentioning
confidence: 99%
“…However, by comparing the R 2 values, it can be determined that the adsorption behavior of 18PZ5A was more consistent with PFO and E, given that they had the same value. The PFO model assumes that adsorption is based on the adsorption capacity of the adsorbent [62], and the E model is generally applied in chemisorption processes; it assumes that the active sites of the adsorbent are heterogeneous [63]. From the value of R 2 , it cannot be determined which model better describes the adsorption since it is an independent criterion [64].…”
Section: Adsorption Isotherms Of As(v) On 11z5amentioning
confidence: 99%
“…Recent reports have shown that heavy metals, even at a minimal concentration, could be detrimental to life forms [1][2][3]. Due to their highly toxic nature and their inability to undergo degradation, they have become a global concern and a major target for most scientists [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their highly toxic nature and their inability to undergo degradation, they have become a global concern and a major target for most scientists [4][5][6]. These metals have also been found in living cells [1]. Within living organisms, they tend to accumulate, binding to nucleic acids and proteins, thereby disrupting essential cellular functions and causing severe health consequences [1,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are the Yan model, the Bohart-Adams model, and the Clark model. They are used to illustrate the breakthrough contaminant curves in the statistical regression column test(Tsvetanova et al, 2022).…”
mentioning
confidence: 99%